Utrjevanje aluminija in zlitin pri vzdolžnem hladnem valjanju - Vasevska, Trajanka (Materiali in tehnologije, 2004)
When using longitudinal cold strip rolling of aluminium and its alloys the deformation direction is changed by 180 compositum. The influence of rolling-direction change on the mechanical properties and the microstructure of aluminium was investigated.
Keywords: hladno valjanje; aluminijeve zlitine; aluminium alloy; mehanske lastnosti; plastična deformacija; mikrostruktura